MVVM in Delphi : architecting and building model view ViewModel applications. - Kouraklis, John (Apress, 2016)
Showing you how to build modern Windows applications, and prepare for cross-platform development, this book introduces you to the right mindset and demonstrates suitable methodologies that allow for quick understanding of the MVVM paradigm. --